Fontes proteicas e idades de abate sobre a estrutura e ultraestrutura do intestino delgado de leitões desmamados - Thomaz, Maria Cristina [UNESP]; Silveira, Antonio Carlos [UNESP]; Kronka, Rodolfo Nascimento [UNESP]; Nakaghi, Laura Satiko Okada [UNESP]; Budiño, Fábio Enrique Lemos (My University, 2011)
Two experiments (experiment 1 - conventional feeding and experiment 2 - feeding of the sows, starting at 109 days of pregnancy and during lactation, and the lactating piglets, with rations without soybean meal) were conducted to evaluate the effects of sources of protein (soybean meal-SBM, extruded semi-integral soybean-ESISB, and milk products-MP) on the intestinal morphology of piglets slaughtered at the 0, 5 and 15 days later at weaning. Twenty-seven piglets weaned with 25 days of age were used, being nine piglets slaughter in each slaughtering age. A 3 ×3 factorial (3 diets × 3 slaughtering ages) was studied, according to a randomized block design. The results showed that animals receiving SBM, presented lower values of villi height and villus: crypt ratio when compared to those that received ESISB or MP. The villi height and the villus: crypt ratio were not affected by the differential feeding of the sows and of the piglets before the weaning. The depth of the crypt was not affected by diets or slaughtering ages in none of the segments studied being, however, smaller in the duodenum and bigger in the jejunum and ileo of the animals of exp. 2. It was concluded that the SBM was the affected the height of the villi and the relationship villi: Crypt negatively after it weans. The intestinal morphology was more affected at five days, showing signals of recovering at 15 days after weaning and that the feeding of the sows did not affect the morphology of the segments of the thin intestine.
Sources of protein and slaughtering ages on the structure and ultra structure of the small intestine of weaned piglets
Keywords: Extruded semi-integral soybean; Intestinal morphology; Milk Products; Soybean Meal; Swine; Animalia; Glycine max; Suidae